Genome-Wide Analysis of the Malaria Parasite Plasmodium falciparum Isolates From Togo Reveals Selective Signals in Immune Selection-Related Antigen Genes - Kassegne, Kokouvi; Komi Koukoura, Komi; Shen, Hai-Mo; Chen, Shen-Bo; Fu, Hai-Tian; Chen, Yong-Quan; Zhou, Xiao-Nong; Chen, Jun-Hu; Cheng, Yang (Frontiers in Immunology, 2020)
Malaria is a public health concern worldwide, and Togo has proven to be no exception. Effective approaches to provide information on biological insights for disease elimination are therefore a research priority. Local selection on malaria pathogens is due to multiple factors including host immunity. We undertook genome-wide analysis of sequence variation on a sample of 10 Plasmodium falciparum (Pf) clinical isolates from Togo to identify local-specific signals of selection. Paired-end short-read sequences were mapped and aligned onto > 95% of the 3D7 Pf reference genome sequence in high fold coverage. Data on 266 963 single nucleotide polymorphisms were obtained, with average nucleotide diversity π = 1.79 × 10−3. Both principal component and neighbor-joining tree analyses showed that the Togo parasites clustered according to their geographic (Africa) origin. In addition, the average genome-wide diversity of Pf from Togo was much higher than that from other African samples. Tajima’s D value of the Togo isolates was −0.56, suggesting evidence of directional selection and/or recent population expansion. Against this background, within-population analyses identifying loci of balancing and recent positive selections evidenced that host immunity has been the major selective agent. Importantly, 87 and 296 parasite antigen genes with Tajima’s D values > 1 and in the top 1% haplotype scores, respectively, include a significant representation of membrane proteins at the merozoite stage that invaded red blood cells (RBCs) and parasitized RBCs surface proteins that play roles in immunoevasion, adhesion, or rosetting. This is consistent with expectations that elevated signals of selection due to allele-specific acquired immunity are likely to operate on antigenic targets. Collectively, our data suggest a recent expansion of Pf population in Togo and evidence strong host immune selection on membrane/surface antigens reflected in signals of balancing/positive selection of important gene loci. Findings from this study provide a fundamental basis to engage studies for effective malaria control in Togo.